Routing and wavelength assignment vs. wavelength converter placement in all-optical networks. - Li, Bo
Blocking has been the key performance index in the design of an all-optical network. Existing research demonstrates that an effective routing and wavelength assignment strategy and a proper wavelength converter placement algorithm are the two primary vehicles for improving the blocking performance. However, these two issues have largely been investigated separately in that the existing RWA algorithms have seldom considered the presence of wavelength conversion, while the wavelength converter placement algorithms have largely assumed that a static routing and random wavelength assignment algorithm is employed. The main objective of this article is to present some strong evidence that these two issues need to be considered jointly, and call for the reexamination of both RWA and wavelength converter placement.
Keywords: All-optical networks; Blocking; Performance index; Routing; Wavelength assignment; Wavelength converter placement; Wavelength converter placement algorithm; Wavelength-division multiplex